Asian women in top management: eight country cases - Yonjoo, Cho; McLean, Gary N.; Amornpipat, Iratrachar; Wei, Wen Chang; Hewapathirana, Gertrude I.; Horimoto, Mayuko; Lee, Mimi Miyoung; Li, Jessica; Manikoth, Nisha N.; Othman, Jamilah; Hamzah, Siti Raba'ah (Routledge, 2015)
This article is a by-product of an innovative session of the 2014 Asia Chapter of the Academy of Human Resource Development conference, Seoul, South Korea, where eight female researchers with roots in eight Asian countries (in alphabetical order: China, India, Japan, Korea, Malaysia, Sri Lanka, Taiwan, and Thailand), presented on the topic of Asian women in top management. In this article, [the authors] present these presenters' perspectives on the topic, including their current state of working conditions and balancing of personal and professional lives. [The authors] asked [the presenters] the following three questions: (1) do traditional values/religious beliefs limit or liberate women in management?; (2) how have social views on the role of women in management changed in [the presenter's] country?; and (3) what organizational and social changes are necessary for women to advance to leadership positions? [The authors] also encouraged [the presenters] to go beyond answering these three questions. Additionally, [the authors] discuss convergence (commonalities) and divergence (differences) across these eight Asian countries.